1963
DOI: 10.1139/v63-095
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Aluminum–oxygen–carbon System

Abstract: A differential thermal analysis technique was used to study the carbothermic reduction of aluminum oxide a t reduced pressures in the temperature range 1700-2200" K. The reduction was found to proceed through the intermediate oxycarbide A1404C, identified by previous workers, to the aluminum carbide. The A140aC and another oxycarbide, AlZOC, were formed by a direct solid-solid reaction, rather than by formation of a gaseous aluminum suboxide and subsequent reaction with carbon as has been postulated.The carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

1964
1964
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 7 publications
4
46
0
Order By: Relevance
“…40 Optical pyrometry offers a convenient, contactless method of measuring temperature without perturbing a microwave field. However, given the sealed tube reaction configuration shown in Figure 1, it proved impossible to obtain valid temperature values using this method.…”
Section: -41mentioning
confidence: 99%
See 1 more Smart Citation
“…40 Optical pyrometry offers a convenient, contactless method of measuring temperature without perturbing a microwave field. However, given the sealed tube reaction configuration shown in Figure 1, it proved impossible to obtain valid temperature values using this method.…”
Section: -41mentioning
confidence: 99%
“…40,41 The reasons for the preferential formation of oxides and oxycarbides under such conditions can perhaps be explained by the reaction processes that may occur in the presence of oxygen (Table 3). [40][41][42] The extremely high enthalpy and Gibbs free energy values for the oxide and oxycarbide phases strongly support the observed requirement for an oxygen-free environment. Moreover, the oxycarbide phase Al2OC has been observed to appear in carbon-rich environments 44 which may also be explained by the solid phase reaction given below (equation 2).…”
Section: -41mentioning
confidence: 99%
“…Unfortunately, no reliable experimental results have been reported so far, although Cox and Pidgeon (10) reported experimental values on the basis of a small change in DTA curve. As we discussed in I, A12OC can be stabilized by forming solid solutions with the isostructural compounds such as aluminum nitride and/or silicon carbide.…”
Section: Chemical Thermodynamics Of Volatilizationmentioning
confidence: 99%
“…[3][4][5] Thermodynamic studies on the system have revealed that the reduction of alumina is controlled by the formation of aluminium sub-oxide vapors. 6) Some studies have been reported on experimental investigations on the carbothermic reduction under vacuum conditions. 7,8) Frank et al have reported on the occurrence of carbothermic reduction of alumina in the temperature range 1 973 K to 2 073 K in the presence of a metallic solvent (Cu and Sn) at pressures between 0.08 to 0.20 atm.…”
Section: Introductionmentioning
confidence: 99%